Contributo para a compreensão atual do mandado de determinação em direito penal: uma perspectiva dos direitos humanos - Correa, Eduardo Pitrez de Aguiar (2011)
This research focuses on one of the norms of the principle of criminal legality, the legal certainty - lex certa. To address the theme, it assumes that the determinacy is an undetermined concept. Instead of analyzing criminal offenses separately, or according to the classification that the jurisprudence assigns to them in relation with legality, the study seeks to contribute to a possible theory of the subject matter, according to the Rule of Law within a Human Rights Protection System. Through the inclusion of negative and positive limits to the object of the study, taking into account its original understanding, the overcoming of utopian rationalism, and a contemporary approach to its grounds, this study aims at providing guidelines to the effective control of the certainty in criminal law. In this search, the investigation looks at the way the American Supreme Court and, especially, the American and the European Courts of Human Rights deal with the problem of indeterminacy of the criminal law, in order to collect elements for an approach in accordance with the Brazilian constitutional and criminal legal system.